Raw Material Inventory Planning Tire Retreading With Silver Heuristic Method Meal In Cv. Xyz - Muhammad Zakaria; Syukriah; Muhammad Yasir (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2018)
This study aims to do the planning of raw material inventory at optimal Tire Retreading industry with Silver Meal Heuristic methods optimally. Planning includes penentian safety stock,, reorder point and Economic Order Quantity and Total Cost of Inventory. The results were obtained 706.44 kg of safety stock, reorder point 2283.76 kg and 8356 kg economic order quantity and lead time of 5 days for a total of Rp. 4,020,778,592.6. While based on the existing condition of the total cost of raw material inventory Rp. 4,061,927,100. This shows the efficiency of Rp. 41,148,507.4 or 1.01% per year.